Gut microbiota diversity but not composition is related to saliva cortisol stress response at the age of 2.5 months. (3rd September 2021) - Keskitalo, Anniina; Aatsinki, Anna-Katariina; Kortesluoma, Susanna; Pelto, Juho; Korhonen, Laura; Lahti, Leo; Lukkarinen, Minna; Munukka, Eveliina; Karlsson, Hasse; Karlsson, Linnea
Abstract: Human brain and intestinal microbes reportedly maintain a constant bidirectional connection through diverse neural, endocrine, immune, and metabolic pathways. Increasing evidence indicates that this communication system, referred to as microbiota-gut-brain axis, enables the gut microbes to influence several aspects of brain function and behavior, including hypothalamic-pituitary-adrenal (HPA) axis stress responses, and on the other hand, stress can affect gut microbiota. However, the role of gut microbiota in the HPA axis functioning in humans remains to be specified especially in early life. This study aimed at identifying the potential link between the cortisol stress response and the gut microbiota at the age of 2.5 months. Fecal microbiota profiles were acquired by 16S rRNA gene sequencing, while salivary cortisol responses after an exposure to a mild acute stressor represented the HPA axis reactivity. We observed that a blunted cortisol stress response was weakly associated with a diverse gut microbiota diversity at the age of 2.5 months. Gut microbiota composition was not associated with cortisol stress responsiveness, but rather with covariates, i.e. factors that influence gut microbiota composition and colonization. LAY SUMMARY: This exploratory study aimed at identifying possible links between cortisol stress responses and fecal microbiota composition in early infancy. In a well-characterized study population of 2.5-month-old infants, we observed that an attenuated cortisol stress responsiveness after a mild stressor was weakly associated with a diverse fecal microbiota. Our results suggest that the gut microbiota composition is associated with environmental factors, such as delivery mode and number of siblings, rather than with cortisol stress responsiveness, in this age group.